Novel loss of function mutation in TUBA1A gene compromises tubulin stability and proteostasis causing spastic paraplegia and ataxia - Zocchi, Riccardo; Bellacchio, Emanuele; Piccione, Michela; Scardigli, Raffaella; D’Oria, Valentina; Petrini, Stefania; Baranano, Kristin; Bertini, Enrico; Sferra, Antonella (Frontiers in Cellular Neuroscience, 2023)
Microtubules are dynamic cytoskeletal structures involved in several cellular functions, such as intracellular trafficking, cell division and motility. More than other cell types, neurons rely on the proper functioning of microtubules to conduct their activities and achieve complex morphologies. Pathogenic variants in genes encoding for α and β-tubulins, the structural subunits of microtubules, give rise to a wide class of neurological disorders collectively known as “tubulinopathies” and mainly involving a wide and overlapping range of brain malformations resulting from defective neuronal proliferation, migration, differentiation and axon guidance. Tubulin mutations have been mainly linked to neurodevelopmental defects, but growing evidence demonstrates that perturbations of tubulin functions and activities may also drive neurodegeneration. In this study, we causally link the previously unreported missense mutation p.I384N in TUBA1A, one of the neuron-specific α-tubulin isotype I, to a neurodegenerative disorder characterized by progressive spastic paraplegia and ataxia. We demonstrate that, in contrast to the p.R402H substitution, which is one of the most recurrent TUBA1A pathogenic variants associated to lissencephaly, the present mutation impairs TUBA1A stability, reducing the abundance of TUBA1A available in the cell and preventing its incorporation into microtubules. We also show that the isoleucine at position 384 is an amino acid residue critical for α-tubulin stability because the introduction of the p.I384N substitution in three different tubulin paralogs reduces their stability and assembly into microtubules, increasing propensity to aggregation. Moreover, we demonstrate that inhibition of the proteasome degradative systems increases the protein levels of mutant TUBA1A, promoting the formation of aggregates that, as their size increases, coalesce into inclusions that precipitate within the insoluble cellular fraction. Overall, our data describe a novel pathogenic effect of p.I384N mutation that differs from the previously described substitutions in TUBA1A, and demonstrate that TUBA1A haploinsufficiency causes neurodegeneration in humans.